Rate‐Dependent Decohesion Modes in Graphene‐Sandwiched Interfaces. Issue 23 (11th October 2019) - Xu, Chaochen; Yang, Tianhao; Kang, Yilan; Li, Qunyang; Xue, Tao; Liechti, Kenneth M.; Huang, Rui; Qiu, Wei
Abstract: Mechanical dry transfer of large‐area graphene is increasingly applied in fabrication of graphene‐based electronic devices, and adhesion energy of graphene/substrate interface is a key factor affecting reliability and performance of these devices. Herein, the adhesion energy of a graphene/poly(ethylene terephthalate) (PET) interface is measured by widely adopted double cantilever beam (DCB) fracture tests. Results show that the apparent adhesion energy of sandwiched interface is highly rate‐dependent. When separation rate increases from 20 to 150 µm s −1, apparent adhesion energy increases by an order of magnitude. By examining fractured interfaces after DCB tests with micro‐Raman spectroscopy, the graphene is found to be fractured and transferred in fragments, with residual tensile strain up to 3% for high separation rates. The results are contrary to earlier reports, where higher separation rate in dry‐transfer process would typically enhance the dry transfer of graphene, resulting in better integrity and performance. Based on Raman spectroscopy measurements, three distinct decohesion modes are identified for PET‐/graphene‐/adhesive‐sandwiched interface, which consistently explain the rate‐dependent apparent adhesion energy. The complicated decohesion modes also suggest that an optimal separation rate should be used to properly measure the adhesion energy and improve the dry‐transfer technique of graphene with minimum damage and residual strain. Abstract : Adhesion energy of graphene/substrate is measured using double cantilever beam method at different separation rates dry transferring the graphene. Significant rate‐dependence is observed and three interface decohesion modes are identified involving graphene fracture and residual straining to explain the rate‐dependence. This work provides a guideline for choosing optimal separation rate in dry‐transfer technique to obtain graphene with better integrity and uniformity.